KARAKTERISTIK ARANG KULIT BUAH KAKAO YANG DIHASILKAN DARI BERBAGAI KONDISI PIROLISIS - Loppies, Justus Elisa (Jurnal Industri Hasil Perkebunan, 2016)
characteristics are determined by main components of the constituent materials, techniques, and pyrolysisconditions. This study aims to determine the characteristics of cocoa pod husk charcoal. The method usedto produce charcoal is carbonization (pyrolysis) process on various conditions. The observed parameterswere temperature and duration of pyrolysis process which is adjusted to obtain charcoalâs maximumquality. Determining parameters of charcoalâs characteristics is caloric value, fixed carbon, volatile, watercontent, and ash. The research shows that to obtain high quality charcoal, 4 â 5 kg cocoa pod husk isprocessed in 350oC during 2 hours. The charcoalâs quality and characteristics processed in 350oC gainoptimum caloric value 6,500 â 7,600 kcal/kg, total carbon 42.57 â 45.53%, volatile matter 30.14 â 32.98%,ash content 16.21 â 16.22%, and water content 6.25 â 8.44%.Keywords: charcoal, characteristics, cocoa pod husks, pyrolysis